Analysis Of The Effect Of Gross Regional Domestic Product, Provincial Minimum Wage, Human Development Index And Investment On Unemployment In Jambi Province - Hierdawati, Trie; Santoso, Agus; Dani , Rian (Jurnal Ekonomi, 2024)
This research aims to determine the influence of Gross Regional Domestic Product, Provincial Minimum Wage, Human Development Index and Investment on Unemployment in Jambi Province. The research method used in this research is a secondary data analysis method with a quantitative approach. Research results: Partially, the provincial minimum wage (X2) has a significant and positive effect on unemployment in Jambi Province and investment (X4) has a significant and negative effect on unemployment in Jambi Province, while gross regional domestic product (X1) and human development index (X3) capital expenditure do not significant effect on unemployment in Jambi Province. However, together Gross Regional Domestic Product (X1), Provincial Minimum Wage (X2), Human Development Index (X3) and Investment (X4) have a significant effect on unemployment in Jambi Province with an R-square value of 74.50 percent during the period 2010-2022